Gene expression and DNA methylation altering lead to the high oil content in wild allotetraploid peanut (A. monticola) - Liu, Nian; Wu, Bei; Pandey, Manish K.; Huang, Li; Luo, Huaiyong; Chen, Yuning; Zhou, Xiaojing; Chen, Weigang; Huai, Dongxin; Yu, Bolun; Chen, Hao; Guo, Jianbin; et al. (Frontiers in Plant Science, 2022)
Introduction The wild allotetraploid peanut Arachis monticola contains a higher oil content than the cultivated allotetraploid Arachis hypogaea. Besides the fact that increasing oil content is the most important peanut breeding objective, a proper understanding of its molecular mechanism controlling oil accumulation is still lacking. Methods We investigated this aspect by performing comparative transcriptomics from developing seeds between three wild and five cultivated peanut varieties. Results The analyses not only showed species-specific grouping transcriptional profiles but also detected two gene clusters with divergent expression patterns between two species enriched in lipid metabolism. Further analysis revealed that expression alteration of lipid metabolic genes with co-expressed transcription factors in wild peanut led to enhanced activity of oil biogenesis and retarded the rate of lipid degradation. In addition, bisulfite sequencing was conducted to characterize the variation of DNA methylation between wild allotetraploid (245, WH 10025) and cultivated allotetraploid (Z16, Zhh 7720) genotypes. CG and CHG context methylation was found to antagonistically correlate with gene expression during seed development. Differentially methylated region analysis and transgenic assay further illustrated that variations of DNA methylation between wild and cultivated peanuts could affect the oil content via altering the expression of peroxisomal acyl transporter protein (Araip.H6S1B). Discussion From the results, we deduced that DNA methylation may negatively regulate lipid metabolic genes and transcription factors to subtly affect oil accumulation divergence between wild and cultivated peanuts. Our work provided the first glimpse on the regulatory mechanism of gene expression altering for oil accumulation in wild peanut and gene resources for future breeding applications.